Identification of Carbohydrates Metabolic Related Enzymes for Lipid Production in Botryococcus sp., a Microalgae Isolated from Taman Negara Endau Rompin: Carbohydrates metabolic enzymes for lipid production - ZUBAINATU ABBA; SITI FATIMAH ZAHARAH MOHAMAD FUZI; HAZEL MONICA MATIAS-PERALTA (Borneo Journal of Resource Science and Technology, 2023)
Botryococcus is a microalgal genus known for its ability to generate and accumulate substantial amounts of lipids via carbohydrate metabolism. This work determined the metabolic pathways and enzymes involved in carbohydrate metabolism leading to increased synthesis of fat in Botryococcus sp. Relevant intracellular and extracellular metabolites were extracted and quantified using chromatographic analysis. Enzymes involved in carbohydrate metabolism leading to lipid formation in Botryococcus sp. under natural conditions were also discovered by one-dimensional gel electrophoresis followed by proteomic mass spectrometry (LC-MS/MS) and database searching. Proximate analysis demonstrated 23.0% total carbohydrate, 16.0% protein and 61.0% lipid per milligram biomass dry weight of Botryococcus sp. The extracellular metabolites constitute mostly of cyclohydrocarbons, nitrogenated hydrocarbons, siloxanes, phenols, and phenol derivatives. A glycolytic enzyme “enolase,” which can create phosphoenolpyruvate and subsequently convert it into pyruvate, was found in this study. This study revealed that enolase provided an alternate pathway to export fixed carbon to the cytoplasm, hence providing a shorter route to lipid production than the normal process via the plastid leading to the manufacture of more lipids in the cells of Botryococcus sp. than other microalgae of the same group.